(untitled) - Beaty, H. Wayne (New York, 1998)
It thoroughly covers updated traction applications, the latest on solid-state motor-drive controllers, electrical and mechanical parameters, specifications, shapes, performance, protection, and every size of motor made--from those used in portable CDs to the motors required by heavy industry.
Keywords: Electric motors,Động cơ điện; Handbooks, manuals, etc.,Sách hướng dẫn